Life-Course Perspective on Immigrant Loneliness: A Conceptual Framework for Intergenerational Loneliness Trajectories - Cifci, Fatmanur (The Family journal (Alexandria, Va.), 2024)
Feelings of loneliness can impact the relationships between the generations and family members. Loneliness among immigrant family members and its generational transmission are attracting more and more attention from academics. Nonetheless, existing research is frequently lacking theoretical foundations. I provide the life-course approach as a framework for enhancing future studies and theories of intergenerational loneliness in members of immigrant families. Particularly, the life-course perspective emphasizes the significance of considering the influence of both an individual's life course, societal factors, linked lives across generations, and the historical context. I review key dimensions of the life-course perspective and make recommendations for future directions in immigrant research on loneliness, generational loneliness disparities, and the transmission of loneliness across generations.